Surface potential and temperature effect studies of homo- and copolysiloxanes through Langmuir Blodgett technique - Faridah Lisa Supian (Tanjong Malim, 2019)
Surface potential and temperature effect studies of homo- and copolysiloxanes through Langmuir Blodgett technique by Faridah Lisa Supian